Revolution without evolution: The 'Way' of change in Ayi Kwei Armah's Two Thousand Seasons. Issue 4 (2nd October 2017) - Guendouzi, Amar
ABSTRACT: Much has been written on Ayi Kwei Armah's disavowal of African revolution/independence and his radical imaginative recreation of African past in his early and middle fiction respectively. However, even when his radical, Afrocentric discourse is underscored and his mythical (re)construction of the black nation's past is unveiled, they are not linked to the Eurocentric philosophies against which they are deployed. This article, therefore, seeks to track the call for change in Armah's middle works, and to reread his narrative and discourse in Two Thousand Seasons in contradistinction to western progressive thought and evolutionary ethics, which spawned western historicism and legitimated imperialism in the 19 th century. Approached from this perspective, Armah's ideological and ethical construct of 'the Way' acquires an additional meaning, and his yearning for a true revolutionary change achieves a wider and more concrete sense.